Age, growth and harvestable size of Cirrhinus mrigala from the Jawahar Sagar Dam, Rajasthan, India - Sarang, N; Sharma, L L; Saini, V P (Indian Journal of Fisheries, 2016)
Age, growth and harvestable size of Cirrhinus mrigala from Jawahar Sagar Dam, Rajasthan, were determined using the key scales. Maximum three annual rings were found and used to assess various growth characteristics. These growth parameters indicated higher value of index of population weight growth intensity (QCW =7.43 g) and index of species average size (Qh =15.83 cm). The calculated weight of fish (Wg) was found to increase upto the third year of life. On the basis of growth parameters studied, a harvestable size of 66 cm has been assigned for Cirrhinus mrigala from the Jawahar Sagar Dam.